Obsessive-Compulsive Disorder with Suicide Obsessions in a First Responder without Previous Diagnosis of OCD or History of Suicide Attempts - Rachamallu, Vivekananda; Song, Michael M.; Liu, Haiying; Giles, Charles L.; McMahon, Terry (Case Reports in Psychiatry, 2017)
Obsessive-compulsive disorder (OCD) is a distressing and often debilitating disorder characterized by obsessions, compulsions, or both that are time-consuming and cause impairment in social, occupational, or other areas of functioning. There are many published studies reporting higher risk of suicidality in OCD patients, as well as studies describing increased risk of suicidality in OCD patients with other comorbid psychiatric conditions such as major depressive disorder (MDD) and posttraumatic stress disorder (PTSD). Existing case reports on OCD with suicide as the obsessive component describe patients with long standing diagnosis of OCD with suicidal ideations or previous suicide attempts. This report describes the case of a 28-year-old male, who works as a first responder, who presented with new onset symptoms characteristic of MDD and PTSD, with no past history of OCD or suicidality who developed OCD with suicidal obsessions. Differentiating between suicidal ideation in the context of other psychiatric illnesses and suicidal obsessions in OCD is critical to ensuring accurate diagnosis and timely provision of most appropriate treatment. The combination of exposure and response prevention therapy and pharmacotherapy with sertraline and olanzapine was effective in helping the patient manage the anxiety and distress stemming from the patient’s OCD with suicidal obsession.